Manufacture of vinyl acetate monomer a plant design - Cezar, Norlito D.; Fontanos, Psyche M.; Nuque, Anna Karenina R.; Relizan, Glenda E. (Diliman, Quezon City College of Engineering, 1998)
Product: Vinyl acetate monomer -- Selling price: Php 55.00/kg -- Capacity: 8,500 MT p.a. -- Total project cost: Php 160,475,604.14 -- Return on investment: 27.60% -- Payback period: 2.04 years -- Plant location: Limay Industrial Estate, Limay, Bataan
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design
Keywords: Factories -- Design and construction; Chemical plants; Vinyl acetate